Bridging the Realms of Underworld and Pure Land: An Examination of Datsueba’s Roles in the Zenkōji Pilgrimage Mandala - Saka, Chihiro (Japanese journal of religious studies, 2017)
This article examines the representation of the Buddhist folk deity Datsueba in the Zenkōji Pilgrimage Mandala, which depicts the temple precinct of Zenkōji located in Nagano City. In the popular imagination of hell in Japan, she is known as a terrifying old woman who robs the deceased of their clothes by the Sanzu River, which people are supposed to cross after death. In the mandala, however, Datsueba is not represented in the scene of hell; she appears on either side of the middle gate leading to the main worship hall, where pilgrims expect to experience ritual death and rebirth and establish karmic connection with Amida Buddha. I argue that Datsueba’s association with death and hell shifts to indicate the salvation that is possible at Zenkōji. Moreover, she signals certain customs and ritual practices which are important at Zenkōji but unable to be directly illustrated in the mandala.